Penerapan Strategi Pembelajaran Aktif Tipe Everyone Is A Teacher Here (ETH) Untuk Meningkatkan Hasil Belajar Siswa Kelas V SD Inpres BTN Pemda Kota Makassar - Kadariah, Kadariah (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2018)
This research is descriptive which generally aims (1) to know the description of the implementation of active learning strategy type ‘Everyone is a Teacher Here’ (ETH) in the learning of fifth grade students of SD Inpres BTN Pemda in Makassar City (2) to know the Implementation of Active Learning Strategy type ‘Everyone is a Teacher Here’ (ETH) in improving learning outcomes of fifth grade students of SD Inpres BTN Pemda in Makassar City. The subjects of this study were 40 students of fifth grade. Data collection techniques used are tests, observation and documentation. Data is processed with qualitative and quantitative descriptive analysis. Data in the form of observations of student activities and teacher activities during the learning process are analyzed qualitatively, and data on learning outcomes of class V students are analyzed quantitatively. The results of the study were used to see the problems that occurred in the school. This is because students are still less active and lack of interaction that occurs in the classroom both between students and teachers, and students and students in the learning process. So that student learning outcomes are still low. Based on the results of research and data analysis conducted shows that the level of student learning outcomes is quite optimal. Based on the individual minimum completeness criteria (KKM) agreed upon, each student must obtain a score of ≥75. The fifth grade student learning outcomes referred to above show that in the initial implementation of teaching activities before the test showed (pre test) the average value of fifth grade students was 63.88 for all subjects. In the teaching implementation process with the implementation of Active Learning Strategy type Everyone is a Teacher Here (ETH) and carried out after the test (post test) showed the average value of fifth grade students increased to 79.86 or above the defined Minimum Examination Criteria (KKM). This shows an increase in learning outcomes of fifth grade students of SD Inpres BTN Pemda Makassar City